Athletic Identity and Performance Anxiety among University Athletes: Moderating role of Perceived Coaching Styles - Fatima Mazhar; Muhammad Faran; Hamza Ameer; Sidra T.M Khan (Psychology in Russia: State of Art)
Background. In the competitive world of emerging athletes, performance is crucial; in sports, it is essential. However, under the spotlight of competition, performance anxiety lurks as the unseen rival every athlete must conquer. Two important factors are fundamental to this dynamic—athletic identity and perceived coaching styles. Athletic identity becomes an athlete’s armor, while the coaching styles catalyze transformation. Their alliance can either elevate performance or diminish it. Objective. To investigate the relationship between athletic identity, perceived coaching styles, and performance anxiety among university athletes. Design. Using a correlational research design, 353 university athletes (191 men, 162 women, aged 18-25, M= 20.8, SD= 1.78) were recruited through non-probability purposive sampling from various universities. The athletic identity measurement scale (AIMS), leadership scale for sports (LSS), and sport anxiety scale-2 (SAS-2) were used to measure the constructs; the athletes also completed a demographic information sheet and provided informed consent. Results. The Pearson product moment correlation results indicated a significant negative correlation between athletic identity and performance anxiety, while perceived coaching styles were significantly positively correlated with performance anxiety. The moderation analyses revealed that training and instruction, social support, democratic behavior, and positive feedback significantly moderated the relationship between self-identity and performance anxiety. Additionally, training and instruction and autocratic behavior significantly moderated the relationship between negative affectivity and performance anxiety. Conclusion. This study underscores the importance of understanding the dynamics between athletic identity, perceived coaching styles, and performance anxiety to optimize athletic performance and reduce performance anxiety among university athletes.